Neural mechanobiology and neuronal vulnerability to traumatic loading - LaPlaca, M. C.; Prado, G. R. (Journal of Biomechanics, 2010)
In order to understand the physical tolerance of neurons to traumatic insults, engineers and neuroscientists have attempted to reproduce the biomechanical environment during a traumatic event using in vitro injury systems with isolated components of the nervous system. This approach allows one to begin to unravel the underlying molecular and biochemical mechanisms that lead to cell dysfunction and death as a function of mechanical inputs. Excess mechanical force and deformation causes structural and functional breakdown, including several key deleterious cellular processes, such as membrane damage, an upset of calcium homeostasis, glutamate release, cell death, and caspase-mediated proteolysis. Understanding of the mechanotransduction events, however, that lead to cellular failure and dysfunction, are not well understood. Mechanically characterized cellular models of traumatic loading are critical to the improved understanding of mechanotransduction in the context of neural injury, the improvement of protective systems, and to provide a controlled setting for testing therapeutic interventions. In this review of the cellular mechanics of traumatic neural loading, we focus on the backdrop and motivation for studying mechanical thresholds in neurons and glial cells and discuss some of the acute responses that may help elucidate improved tolerance criteria and illuminate future research directions.